The Advantages and Disadvantages of Quantitative and Qualitative Approach for Investigating Washback in English Language Testing - Venny Karolina; Muaffi Alif; Sudharni Sudharni (Universitas Pahlawan Tuanku Tambusai, 2021)
This paper aims to analyse the benefit and constraints of approaches for investigating washback in English language testing. This paper starts with the exploration of the concept of washback in English language testing. The notion of washback is related to the effect of testing on learning and teaching. This notion shows that washback research is associated with a causal relationship. A causal relationship might be investigated through quantitative, qualitative, or mixed-method approaches. Each approach may have strengths as well as constraints. This paper concludes that quantitative and qualitative approaches contribute to the investigation of washback in English language testing. However, each approach also has some constraints. This writer concludes that a qualitative approach may suit well to investigate washback in English language testing. This approach may capture in-depth information on how and why teachers and students are affected by language testing in their teaching and learning process. However, the quantitative approach may excel in many participants so that the research results may be generalised. Each approach may contribute to washback research in English language testing; therefore, a mixed-method approach: qualitative and quantitative, is recommended to gain comprehensive finding for investigating washback in English language testing